Memory, post-socialism and the media: nostalgia and beyond - Sabina Mihelj (2016)
While research on the mediation of post-socialist memory has gained momentum in recent years, the field remains fragmented and limited to small-scale case studies, with little attempt to develop a more general reflection on the nature of the processes investigated. Engagement with the wider literature on the mediatisation of memory has been limited as well, with research typically applying established conceptual frameworks rather than using post-socialist materials to generate new theoretical insights. Given the state of the field, this article has a double aim. First, it offers a critical review of the main trends in existing research, focussing on four key issues: the fascination with nostalgic modes of remembering, the dominance of national frames of analysis, the lack of research on the mediation of personal and vernacular remembering, and the privileging of descriptive over explanatory modes of analysis. Second, the article outlines a new agenda for the field, and proposes three main research trajectories. The first pays attention to how mediated memories at local and national levels interact with transnational processes of remembering the Cold War, the second focusses on to the intersections between personal and public modes of mediated remembering, and the last moves the discussion from description to explanation, using comparative approaches to advance explanations of different modes of mediated post-socialist memories.